And now the screaming really starts! - Hamant Manjit Singh (2011)
This paper engages with the writings of Michel Chion and seeks to study the function of the human scream in cinema. It begins with an essential study of the human scream and the motivations behind it. This inquiry also reveals the relationship between the scream and language systems. The essay then argues against the engendering of cries and proposes that the function of cries should be prioritised. For this purpose, examples from the Alien quadrilogy are used to illustrate how the scream transcends both gender and language. The essay also briefly examines the role of the scream in horror films. Also, the essay studies the human scream in relation to time and investigates the temporal significance of the scream scene. A comparison is presented in this paper between the language of the close-up, according to Béla Balázs, and the inherent linguistic structure of the human scream. The later portions of the paper suggest various means to film a scream scene and puts forth modifications to Chion's theory of the “Screaming Point”. The formal considerations of filming the “scream scene” are discussed, with the hope of establishing the most effective manner to present the “scream scene”. While this essay seems to be heavily engage theoretical concerns, there are also considerations of viewership that are discussed. In some ways, the study of viewership aids in the understanding of the way the human scream functions in cinema. The paper closes with considerations for the future and explores other areas in which studies on the “scream scene” may be developed.